The relationship between acoustic structure and semantic information in Diana monkey alarm vocalization - Riede, Tobias; Zuberbühler, Klaus (My University, 2003)
Mammalian vocal production mechanisms are still poorly understood despite their significance for theories of human speech evolution. Particularly, it is still unclear to what degree mammals are capable of actively controlling vocal-tract filtering, a defining feature of human speech production. To address this issue, a detailed acoustic analysis on the alarm vocalization of free- ranging Diana monkeys was conducted. These vocalizations are especially interesting because they convey semantic information about two of the monkeys’ natural predators, the leopard and the crowned eagle. Here, vocal tract and sound source parameter in Diana monkey alarm vocalizations are described. It is found that a vocalization-initial formant downward transition distinguishes most reliably between eagle and leopard alarm vocalization. This finding is discussed as an indication of articulation and alternatively as the result of a strong nasalization effect. It is suggested that the formant modulation is the result of active vocal filtering used by the monkeys to encode semantic information, an ability previously thought to be restricted to human speech.
Keywords: interspecific communication; anti-predator behaviour; Ivory Coast; primates; associative learning; habituation